PuCRZ1, an C2H2 transcription factor from Polyporus umbellatus, positively regulates mycelium response to osmotic stress - Han, Pengjie; Hua, Zhongyi; Zhao, Yuyang; Huang, Luqi; Yuan, Yuan (Frontiers in Microbiology, 2023)
Polyporus umbellatus is an edible and medicinal mushroom with the capacity to produce sclerotia. However, the mechanism of P. umbellatus sclerotia formation is unclear. CRZ1 is a C2H2 family transcription factor involved in the Ca2+-calcineurin signaling pathway, which has the function of regulating sclerotia formation, maintaining ion homeostasis, and responding to stress. In this study, we identified 28 C2H2 transcription factors in P. umbellatus genome, 13 of which are differentially expressed between mycelium and sclerotia, including PuCRZ1. Combining DNA affinity purification and sequencing (DAP-seq) and RNA sequencing (RNA-seq), three genes (PuG10, PuG11, PuG12) were identified as putative PuCRZ1 target genes containing a putative binding motif (GTGGCG) within their promoter. Yeast single hybridization (Y1H) and EMSA further confirmed that PuCRZ1 can bind to the promoter region of PuG10, PuG11, and PuG12. PuCRZ1 gene could reduce the sensitivity of NaCl in yeast cells. Furthermore, overexpression of the PuCRZ1 target gene, especially the FVLY domain containing gene PuG11, could improve the mycelia growth rate and mannitol tolerance in P. umbellatus. These results demonstrate that PuCRZ1 in the Ca2+-calcineurin signaling pathway plays an important role in mycelia growth, as well as osmotic stress tolerance.